Adsorption in Reversed Order of C2 Hydrocarbons on an Ultramicroporous Fluorinated Metal‐Organic Framework. (25th April 2022) - Yang, Lingzhi; Yan, Liting; Niu, Weijing; Feng, Yan; Fu, Qiuju; Zhang, Shuo; Zhang, Yinhang; Li, Liangjun; Gu, Xin; Dai, Pengcheng; Liu, Dandan; Zheng, Qingbin; et al.
Abstract: Metal‐organic frameworks have been widely studied in the separation of C2 hydrocarbons, which usually preferentially bind unsaturated hydrocarbons with the order of acetylene (C2 H2 )>ethylene (C2 H4 )>ethane (C2 H6 ). Herein, we report an ultramicroporous fluorinated metal‐organic framework Zn‐FBA (H2 FBA=4, 4′‐(hexafluoroisopropylidene)bis(benzoic acid)), shows a reversed adsorption order characteristic for C2 hydrocarbons, that the uptake for C2 hydrocarbons of the framework and the binding affinity between the guest molecule and the framework follows the order C2 H6 >C2 H4 >C2 H2 . Density‐functional theory calculations confirm that the completely reversed adsorption order behavior is attributed to the close van der Waals interactions and multiple cooperative C−H⋅⋅⋅F hydrogen bonds between the framework and C2 H6 . Moreover, Zn‐FBA exhibits a high selectivity of about 2.9 for C2 H6 over C2 H4 at 298 K and 1 bar. The experimental breakthrough studies show that the high‐purity C2 H4 can be obtained from C2 H6 and C2 H4 mixtures in one step. Abstract : An ultramicroporous fluorinated metal‐organic framework (MOF) shows a reversed adsorption order for C2 hydrocarbons. The C2 hydrocarbon uptake of the framework and the binding affinity between the guest molecule and the framework follow the order C2 H6 >C2 H4 >C2 H2 and not the usual C2 H2 >C2 H4 >C2 H6 .